(untitled) (IUBAT Review, 2025)
This study presents the development and validation of a low-cost, computer-controlled device for measuring surface wettability through contact angle analysis. The instrument comprises electro-mechanical components operated by an Arduino Uno microcontroller, including a high-precision syringe pump, a 3-axis motorized workbench, and a mobile camera with a 100 mm macro lens. Surface preparation involved polishing, cleaning, and drying to ensure repeatable conditions. Water droplets (2–10 µL) were dispensed and withdrawn on aluminum, copper, brass, steel, and glass substrates under ambient laboratory conditions. Static and dynamic contact angles were extracted from 40 high-resolution images obtained from 30 fps video recordings and analyzed using ImageJ and MATLAB. The device achieved static contact angle measurements of 93° ± 2.7° (Al), 85° ± 6.35° (Cu), 25.0° ± 6.7° (glass), 88° ± 8.35° (brass), and 87° ± 5° (steel), with deviations from literature values ranging from 1.93° to 4.97°. Dynamic analysis indicated higher contact angle hysteresis for copper and brass ( 34°), while glass showed the lowest ( 21°) at a flow rate of 0.8 µL/s. The instrument demonstrated high measurement precision, with uncertainties of ±3.5° for imaging and ±0.2° for angle calculation, validating it as an accurate and cost-effective alternative to commercial goniometers. IUBAT Review—A Multidisciplinary Academic Journal, 8(1): 96-112